WAIS Divide Ice-Core Aerosol Records from Intermediate Core WDC05A - Mcconnell, Joseph (IEDA: US Antarctic Program Data Center, 2017)
Abstract: A state-of-the-art continuous ice core analytical system was used to analyze samples from the firn portion (0 to ~70 m depth) of the recently collected intermediate core WDC05A from West Antarctica. Interpretation of these records and publication of findings is ongoing.